Baring all: The impact of the hospital gown on patient well‐being. Issue 3 (20th April 2020) - Morton, Liza; Cogan, Nicola; Kornfält, Susanna; Porter, Zoe; Georgiadis, Emmanouil
Abstract : Objectives: The importance of personalized and dignified care is increasingly being recognized in health care policy and practice. Despite the known impact of clothing on social identity and self‐expression, the impact of hospital clothing on patient well‐being has been widely overlooked. Patients are often required to wear hospital clothing, commonly a backless gown, during medical procedures and surgeries. The impact of wearing patient clothing on well‐being, during this time of vulnerability, was explored. Design: A sequential multi‐method approach consisting of two studies. Methods: Two studies were carried out to consider the impact of the hospital gown on well‐being among adults with and without chronic health conditions. The first study consisted of conducting in‐depth, semi‐structured interviews ( n = 10) with adults living with a lifelong chronic health condition (congenital heart disease). The second study was a cross‐sectional online survey exploring adults' views ( n = 928) and experiences of wearing the hospital gown. Results: Qualitative analysis identified the following master themes: (1) symbolic embodiment of the 'sick' role, (2) relinquishing control to medical professionals, and (3) emotional and physical vulnerability. Quantitative analysis of the online survey data indicated that adults often reported wearing the hospital gown despite a lack of medical necessity. Its design was considered to be not fit for purpose and lacking in dignity. Conclusions: The implications of these findings for health policy and practice are discussed, emphasizing the importance of challenging cultural norms in health care since dehumanizing aspects of care, as symbolically represented by the hospital gown, may adversely impact on patient well‐being. Statement of contribution What is already known Getting dressed is a form of self‐expression, which contributes to the construction of social identity, yet few studies have explored the impact of wearing hospital clothing on patient well‐being. The few studies on hospital clothing that exist suggest it is predominantly associated with feeling depersonalized, stigmatized, and devitalized, being in the 'patient role', low status, and a lack of control and privacy. However, previous studies include a variety of hospital clothing including pyjamas (Edvardsson, 2009) and dressing gowns (Topo & Iltanen‐Tähkävuori, 2010), whereas in the United Kingdom, a 'one‐size‐fits‐all' backless gown, held together with ties at the back, is most commonly used. What this study adds This study furthers understanding about the lived experience of wearing hospital clothing for people living with a chronic health condition (congenital heart disease) and without. Wearing hospital clothing (most commonly the hospital gown) was associated with symbolic embodiment of the 'sick' role, relinquishing control to medical professionals, and emotional and physical vulnerability for people living with a chronic health condition. Findings from a wider sample, drawn from the general population, suggest that the hospital gown is often being used despite a lack of medical necessity often leaving patients feeling exposed, self‐conscious, vulnerable, uncomfortable, cold, embarrassed, and disempowered. These findings are exacerbated for people living with a long‐term health condition and women. Together, these studies suggest that the current design of the hospital gown is not fit for purpose and impacts negatively on patient well‐being.